Aligning Pedagogical Beliefs and Technology Integration in English Language Teaching: A Multiple-Case Study of Islamic Senior High School EFL Teachers - Linda Sari; Effendi Limbong; Yuni Utami Asih (Teacher Training and Education Faculty, Widya Gama Mahakam Samarinda University, 2023)
Understanding how teachers' pedagogical beliefs regarding language teaching and learning have been transferred into technology integration practices in English teaching would assist teachers in optimizing learning outcomes and facilitating teaching-learning. The purpose of this study is to explore how language teachers' pedagogical beliefs, which beliefs about language instruction and learning that have been translated into technology integration in English instructional practice. This study used a case study as the research design, this research also used other instruments, there were interview guidelines, documents checklist, and observation form/field notes. The data analysis of this study consisted of two phases: within-case analysis (phase 1) and cross-case analysis (phase 2). The results of this study showed rule-based practices with technology implemented by teachers. In this study typically entailed using technology to support grammar and practice in the classroom. Also, it showed the purposeful study and assessment or application of grammatical rules within appropriate contexts. Moreover, the integration of Islamic education with science and technology learning is expected to be meaningful and easily understandable. Therefore, the goal of Islamic education in leading students to recognize, understand, contemplate, believe, and have a noble character in implementing the teachings of Islam from the primary source, the holy book of Al-Quran and Al-Hadith, can be accomplished through teaching guidance, practicing, and the use of experience